RESULTS OF SPECIAL-TECHNICAL TRAINING AT THE BEGINNING OF THE PEDAGOGICAL EXPERIMENT ON THE STUDY OF THE EFFECTIVENESS OF DEVELOPING THE BALANCE ABILITY OF AMPUTEE FOOTBALL PLAYERS AND THEIR DISCUSSION - Mirqosimov Mirzoir Mirzoxid’s ugli (The Conference Hub, 2025)
The article focuses on special training and technical preparation during the training phase of amputee football players, and examines the general differences in the results obtained by the players at the beginning of the experiment.
Keywords: Amputee players, technique, physical condition, training, special training, technical training, parasports.